The architectural design practice in the folds of decision-making processes [La pratica della progettazione architettonica nelle pieghe dei processi decisionali] - Elena Todella (Valori e Valutazioni, 2023)
The role of evaluation in urban and architectural design processes is a current field of investigation, in the national context. Scholars in evaluation increasingly focus on the need for opening the “black box” of architectural design process, directing the evaluation discipline in making explicit and communicable its mechanisms. Currently, the role of evaluation in making explicit and communicable the reasons for the choices to be made is often deepened, on the one hand, in terms of exploring the architectural design process as an intellectual, ideational and creative practice, starting from a “generative idea”; on the other hand, in terms of its contribution with respect to the quality of the product – as buildings – in relation with the quality of the project in its drafting practices. This paper reflects on architectural design as a decision-making activity that needs to be unpacked in order to be supported by evaluation through specific tools and methodologies. In doing so, the attention is shifted from the material products of architecture – such as buildings – to the processes of proposal, negotiation and finalization of projects. Consequently, the main aim is a theoretical investigation on the role of some architectural design practices in relation to the ongoing decision-making process, by exploring the connections between these practices and their results and effects in the process.